2019
DOI: 10.1111/are.14103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nucleotides supplementation to low‐fish meal feed on long‐chain polyunsaturated fatty acid composition of juvenile rainbow troutOncorhynchus mykiss

Abstract: A feeding trial was conducted to evaluate the effect of nucleotides supplementation to low‐fish meal feed on growth and fatty acid composition of rainbow trout. Six isonitrogenous (42% crude protein) and isolipidic (18% crude lipid) diets were formulated containing fish meal and plant ingredients as main protein sources. The control diet was a basal diet without supplementation of nucleotides, and five experimental diets were prepared by supplementing one of the five different nucleotides in the form of 5′‐mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
(101 reference statements)
2
8
1
Order By: Relevance
“…Interestingly, our present study clearly showed that dietary pyrimidine nucleotides modulated fatty acid composition in the muscle but not in the liver of rainbow trout mainly for 20:4 n ‐6 and 22:6 n ‐3 contents. This finding was also in accordance with our previous finding on fatty acid composition in the muscle of rainbow trout fed nucleotide‐supplemented diet (Ridwanudin et al, 2019). Liver is a main organ to synthesize fatty acid and convert into other fatty acid or fatty acid derivatives such as eicosanoids and deliver it to other organs via blood circulation (Turchini et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Interestingly, our present study clearly showed that dietary pyrimidine nucleotides modulated fatty acid composition in the muscle but not in the liver of rainbow trout mainly for 20:4 n ‐6 and 22:6 n ‐3 contents. This finding was also in accordance with our previous finding on fatty acid composition in the muscle of rainbow trout fed nucleotide‐supplemented diet (Ridwanudin et al, 2019). Liver is a main organ to synthesize fatty acid and convert into other fatty acid or fatty acid derivatives such as eicosanoids and deliver it to other organs via blood circulation (Turchini et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…However, supplementation of 1.5 g/kg pyrimidine nucleotides in the present study did not show to increase growth performance or feed utilization of rainbow trout. This was also similar to our previous study which found that supplementation of 1.5 g/kg purified nucleotides to low fishmeal‐based diet did not affect growth of rainbow trout (Ridwanudin et al, 2019). No growth promotion effect of 1.0 g/kg dietary nucleotides was also found in the juvenile turbot Scophthalmus maximus L. when fish meal replaced by 300 to 500 g/kg soya bean meal in the diet (Peng et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Several literature heightened attention on the usage of nucleotides as Growth promotor feed additives that are needed particularly for enhancing fish body metabolism and for developing of immune and intestinal tissues. (Peng et al, 2013 andRidwanudin et al, 2019). Nucleotides are low molecular weight biological compounds that play major roles in most biological processes which Can occur as subunit nucleobases or as polymeric nucleic acids (low et al, 2003).…”
Section: Introductionmentioning
confidence: 99%